1995
DOI: 10.1038/ki.1995.117
|View full text |Cite
|
Sign up to set email alerts
|

Expression of protein kinase C isoforms in renal tissue

Abstract: PKC plays a central role for the regulation of renal function. PKC consists of a family of isoenzymes. By employing Northern blot techniques we have demonstrated that mRNA transcripts for the classical Ca(2+)-dependent, diacylglycerol-activated isoform alpha, the novel, Ca(2+)-independent isoform delta and the atypical isoform zeta are abundantly expressed in the rat kidney. The novel PKC-epsilon was weakly expressed. The classical PKCs beta I, beta II and gamma could not be detected. The mRNA expression of PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Numerous studies document the growth-promoting properties of PKC; however, there is increasing evidence that some PKC isozymes are involved in cell growth inhibition and differentiation (reviewed in reference 13). In renal tissue, PKC ␣, ␦, and are the most abundant isozymes, while PKC ε is weakly but uniformly expressed in both the cortex and the medulla during ontogeny (40). Previous studies have shown that activated PKC ε inhibits cell growth in some tissues (32,46).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies document the growth-promoting properties of PKC; however, there is increasing evidence that some PKC isozymes are involved in cell growth inhibition and differentiation (reviewed in reference 13). In renal tissue, PKC ␣, ␦, and are the most abundant isozymes, while PKC ε is weakly but uniformly expressed in both the cortex and the medulla during ontogeny (40). Previous studies have shown that activated PKC ε inhibits cell growth in some tissues (32,46).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrate that the ANG II stimulation of CD renin occurs via a Ca 2ϩ -dependent PKC and that increases in intracellular Ca 2ϩ are not enough to enhance prorenin or renin expression. PKC-␣ is the most abundant isoform present in renal CD cells (33). We used a PKC-␣ dominant negative, which expresses mutated nonfunctional PKC-␣, competing with the normal isoforms to specifically suppress PKC-␣ activity.…”
Section: Discussionmentioning
confidence: 99%
“…All isoforms express distinct enzymological properties, differential tissue distribution, different substrate specificity, and specific subcellular localization with distinct modes of cellular regulation (4,6,9,18,23,36,38). For example, PKC␣, ␦, ⑀, and , but not PKC␤, which is strongly expressed in cardiomycytes, were detected in rat MC as determined by Western blotting (18,19,42).…”
mentioning
confidence: 99%